Research into natural factors of the Trans‐Baikal region influencing air quality of a city located in an intra‐continental intermountain basin: the example of the Tugnui basin - A. P. Shcherbatyuk (Юг России: экология, развитие, 2019)
Aim. The study of the degree of influence of natural factors in the Trans‐Baikal region on the quality of the air of the city of Petrovsk‐Zabaykalsky, which lies in an  intermountain basin.   Material and Methods. The geomorphology and climate of the intermountain basins of the Trans‐Baikal regions, as well as their separation by orographic features,  were studied. Missing points were identified which need for further scientific research regarding the influence of natural factors of the Trans‐Baikal region on the  quality of the air.   Results. Geographical and natural factors in the formation of the qualitative composition of the atmosphere of cities located in intracontinental intermountain basins are presented. Studies were conducted from 2005 to 2015 at three observation  posts (hereinafter – OP) in the city of Petrovsk‐Zabaykalsky (Н1 = 800 m; Н2 = 860  m; Н3 = 895 m). The dynamics of the average values of pollutant content in the air  of  the  city  of  Petrovsk‐Zabaykalsky  for  the  period  2005‐2015  were  considered  (based on field observations from three OPs), as well as the dynamics of the atmospheric pollution index of benzo(a)pyrene in the air in Petrovsk‐Zabaykalsky for the  period 2005‐2015. Geoecological threats were assessed together with the geographical mechanisms responsible for them and the dynamics of atmospheric air  pollution of a characteristic situation (the Tugnui basin and atmospheric air of the  city of Petrovsk‐Zabaykalsky) were studied. The regular occurrence of extremely  dangerous concentrations of pollutants in the atmosphere of cities located in intermountain basins is presented.   Conclusion. The author’s research into the influence of natural factors (using the  example of the Tugnui basin) on the air quality of a city on the National Priority List  (e.g. the city of Petrovsk‐Zabaykalsky) showed that extremely dangerous concentrations of pollutants, especially substances of the first hazard class, namely benzo(a)pyrene, are created because of geographical factors.